Ghrelin and Cardiovascular Diseases - Zhang, Gaigai; Yin, Xinhua; Qi, Yongfen; Pendyala, Lakshmana; Chen, Jack; Hou, Dongming; Tang, Chaoshu (Current Cardiology Reviews, 2010)
Ghrelin, a newly discovered bioactive peptide, is a natural endogenous ligand of the growth hormone (GH) secretagogue receptor and initially identified as a strong stimulant for the release of GH. Subsequent research has shown that ghrelin and its various receptors are ubiquitous in many other organs and tissues. Moreover, they participate in the regulation of appetite, energy, bodyweight, metabolism of glucose and fat, as well as modulation of gastrointestinal, cardiovascular, pulmonary, immune functions and cell proliferation/apoptosis. Increasing evidence has demonstrated that ghrelin has a close relationship with cardiovascular system. Ghrelin and its receptors are widely distributed in cardiovascular tissues, and there is no doubt that the effects of ghrelin in the cardiovascular system are mediated not only via its growth-hormone-releasing effect but also by its direct effects on the heart. Exogenous administration of ghrelin can dilate peripheral blood vessels, constrict coronary artery, improve endothelial function, as well as inhibit myocardial cell apoptosis. So, ghrelin may have cardiovascular protective effect, including lowering of blood pressure, regulation of atherosclerosis, and protection from ischemia/reperfusion injury as well as improving the prognosis of myocardial infarction and heart failure. Some of these new functions of ghrelin may provide new potential therapeutic opportunities for ghrelin in cardiovascular medicine. In this paper, we will review the existing evidence for cardiovascular effects of ghrelin, including the cardiovascular function, the variations in ghrelin plasma levels in pathophysiologicalogical conditions, the possible protective mechanisms of ghrelin, as well as its future potential therapeutic roles.
Keywords: hypertension